Mechanism of Rad26-assisted rescue of stalled RNA polymerase II in transcription-coupled repair - Chunli Yan (Nature Portfolio, 2021)
Here the authors provide models of RNA polymerase II bound to the yeast CSB ortholog Rad26 in different nucleotide states; explain how Rad26 domain motions help the polymerase progress past DNA lesions; and interpret the effects of CSB-associated disease mutations.